Dual Acceptance of Web Diffusion: A Case of Clients and Servers - Chen, Hsiang (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This study introduces the concept of dual acceptance to the diffusion of innovation theory and calls for new modifications to the diffusion of interactive media in the particular case of the Web technology, a client/server architecture. The diffusion of Web clients and Web servers creates a dual acceptance phenomenon and crossed-reciprocal interdependence relationships, which stimulate. . .